MODEL DIGITAL MARKETING YANG BERDAMPAK PADA KINERJA UMKM BERBASIS IT CAPABILITY DAN INOVASI PRODUK PADA UMKM - Haryo Kusumo; Achmad Solechan (Jurnal Manajemen, Bisnis dan Kewirausahaan, 2023)
The research object in this study was MSMEs in Semarang Regency. The aim of this research is to analyze the influence of digital marketing on the performance of MSMEs based on innovation and IT capability. The sample in this study was 114 respondents using a sampling method, namely the area sampling technique by selecting MSMEs in Semarang Regency. There are many sub-districts spread across Semarang Regency, so the sample was determined using quota sampling, namely that MSMEs in each sub-district were taken from 6 MSME actors spread across 19 sub-districts in Semarang Regency. The data collection method used is the questionnaire method and data analysis method using SmartPLS software. The test results show that Hypothesis 1 is accepted because it shows a positive and significant influence on the influence of digital marketing on innovation. Hypothesis 2 is accepted because it shows that there is a positive and significant influence on the influence of digital marketing on IT Capability. Hypothesis 3 is accepted because it shows that there is a positive and significant influence on the influence of Innovation on MSME Performance. Hypothesis 4 is accepted because it shows that there is a positive and significant influence on the influence of IT Capability on MSME Performance. Hypothesis 5 is accepted because it shows that there is a positive and significant influence on the influence of Digital Marketing on MSME Performance.